Thermo-economic evaluation and optimization of solar-driven power-to-chemical systems with thermal, electricity, and chemical storage - Huang, Shengwei; Zhang, Yumeng; Guo, Xinyu; Qian, Meng; Zhao, Yongming; Li, Liang; Zhou, Xing (Frontiers in Energy Research, 2023)
This paper evaluates the thermo-economics of power-to-chemicals using solar energy, with the chemicals being methane, methanol, and gasoline. In addition to the optimal technologies sizing and heat cascade utilization, this paper also considers the optimal molten-salt solar power tower (MSPT) design, as the MSPT significantly affects the levelized product cost. A bi-level optimization employing mixed-integer linear programming at the lower level with heat and mass integration for optimal sizing of technologies and utilities, and genetic algorithms at the upper level for optimizing the MSPT design is proposed. The electricity sources considered are MSPT, photovoltaic (PV) with daily electricity storage, and the electrical grid as complementary technology to satisfy the targeted daily product demand. Cost-compativeness of solar-driven chemicals synthesis is thoroughly assessed via considering sensitivity analysis on (1) regional solar resource endowments and actual local demands; (2) electricity sources,i.e., PV verse MSPT; and (3) the scale effect represented by different chemicals yield. Results show that the levelized methane cost ranges from 4.5--8.5 €/kg, depending on the location, plant size and annual power contribution of concentrating solar power. Due to the larger mass production, the levelized cost of methanol and gasoline is lower: 1.5--2.2 €/kg for methanol and 4--6 €/kg for gasoline. The findings highlight the significance of location choice by observing that direct solar radiation in France is 100 kWh/m2 higher than in Italy which reduces the methane production cost by 2.4 €/kg. Sensitivity analysis performed on plant scale reveals that a compact, small-scale system is far too expensive. The levelized cost of methane could be decreased by 1.2 €/kg when the plant is scaled up from 4000 to 20000 kg/day H2. Due to its expensive electricity storage and limited working hours, PV is typically not chosen as a power source. Overall, solar fuels are unlikely to be cost-competitive in the near future when compared to market prices for all three compounds under consideration.